Classification of the cognitive domain of executive functions and memory in Neuropsi battery - Rivera B., Jóse Carlos (2013)
If tests, psychological instruments or batteries have in common is something that characterizes its construct validity, that is to say, in this case how the set of variables grouped to measure NEUROPSI Battery? Comparatively analyzed the conceptual elements (variables and indicators) of Attention and Memory NEUROPSI 6-85 years, located in two journals, and found that the battery used in the implementation study was a variant of that in the data sheet instrument.